MENGGUNAKAN METODE PARTISIPATORI DENGAN TEKNIK ATTL (AMATI, TANYA, TULIS, LAPORKAN) DALAM UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA PADA PESERTA DIDIK KELAS VIIIA MTs NEGERI 1 KOTABARU TAHUN PELAJARAN 2018/2019 - Ibrahim Muin (STKIP Paris Barantai, 2021)
This study aims to (1) describe the improvement of news text writing skills in class VIIIA MTs Negeri 1 Kotabaru students after participating in participatory learning using the ATTL technique, (2) describe changes in behavior of students class VIIIA MTsN 1 Kotabaru attending learning with a participatory method using the ATTL technique. The method used is a participatory method with the ATTL technique. This research was carried out in two stages, namely cycle I and cycle II. Data cycle I and cycle II test and non-test techniques. Non-test techniques in the form of observation, and interviews. Data analysis techniques were carried out quantitatively and qualitatively. The results of the test completeness in the first cycle were 6.25% average of 36.46 in the poor category. In cycle II, the completeness of students reached 100% with an average of 97.15 very good categories. There was an increase from the first cycle of 93.75%.